How work design shapes mental health in the Healthcare and Social Assistance industry. A report by the Centre for Transformative Work Design at Curtin University and the University of Sydney Business School. - Jolly, Anu; Kunzelmann, Arian; Dey, Shanta; Zettna, Nate; Yam, Cheryl; Forner, Vivien; Askovic, Mina; Johnson, Anya; Nguyen, Helena; Parker, Sharon (2023)
This report spotlights the insights from the ongoing Design for Care research project about the key psychosocial risks in the Healthcare and Social Assistance (H&SA) industry, and aspects of work design that can protect against these risks.